Greek Philosophy Adventure Techniques of Interpreting the World in the Hellenistic Period from Thales to Aristotle (Journal of the College of Basic Education, 2023)
There is one truth in it, which is that philosophy does not cease to read itself and its history continuously, and thisIf anything indicates that it enjoyed vitality throughout its historical course. AlthoughOur research does not aim to provide a new reading of the history of philosophy as much as it will provide a review of interpretation techniques.systems of philosophical thinking that prevailed in the Greeks, especially during the Hellenistic era.This does not mean that we will overlook its history, as it provided us with philosophical models that explained the world through its ages.Historicism, that is, the history of philosophy will be in this study a history of the techniques of interpreting the world byPhilosophers, especially in the Hellenistic period. Philosophy, in its essence, is a discourse on truth, and as one ofThe great images of human thought, as it is a discourse whose purpose is to present a form and meaning to the world to which one belongs.The human being, or the world to which one should belong (such as the world of the Platonic proverb, for example). Philosophy is an attemptA humanity that aims to escape from chaos, dams, and becoming *, by means of (flat drawing and flat formationabove the nebula (1), because what always threatens philosophy lies in confronting that process and nebulae thatEvents move over it for the sake of its understanding (i.e. making it conceptual). Philosophy has caused a displacementAnd a radical shift in the techniques of interpreting the world that prevailed in the ancient East (Iraqi civilizations).Chinese, Iranian and Egyptian) and raised the problem of looking at this problem from a new point of view. He hasThe civilizations of the ancient East used to tell the story of the world and narrate it in a metaphorical way to present an imagined picture of the world.The world in which man resides, i.e. (the wise sheikh comes from the East, he thinks through the imageWhile the philosopher creates the concept and reflects on it). 2